(untitled) - Larsen, E. John (New York, 2006)
"Larsen's Advanced Accounting" provides complete and in-depth coverage of the topics typically taught in a one-or-two semester advanced accounting course, including partnerships, business combinations and consolidated financial statements. Faculty appreciate the current coverage of FASB and GASB regulations, the wealth of thorough end-of-chapter material, and the in-depth coverage in this shorter length Advanced text. Flexibility is provided by modularly designed parts, each self-contained, that allow instructors to cover only chapters that are appropriate for their class.
Keywords: Accounting